GE_GERICHTE A/1705/2019 vom 13. August 2021 - GE Cour de justice (2021)
RETRAIT DE PERMIS;FAUTE GRAVE;ACCIDENT;SIGNALISATION ROUTIÈRE;SIGNAL LUMINEUX;CODE DE PROCÉDURE PÉNALE SUISSE | LCR.16C.al2.leta; LCR.15c.al1.leta; LCR.27.al1